CO2 Reduction by Dry Methane Reforming Over Hexaaluminates: A Promising Technology for Decreasing Global Warming in a Cost Effective Manner - Maria Salazar-Villalpando; Todd H. Gardner (The Minerals, Metals and Materials Society, 2008)
"Efficient utilization of CO2 can help to decrease global warming. Methane reforming using carbon dioxide has been of interest for many years, but recently that interest has experienced a rapid increase for both environmental and commercial reasons. The use of CO2 provides a source of clean oxygen, which eliminates the need for costly oxygen separation plants. The product of dry reforming is useful syn-gas, which can be used to generate electrical power in a SOFC or in the production of synthetic fuels (hydrocarbons and alcohols). Hexaaluminate catalysts prepared at NETL may represent a product that can be utilized for the conversion of CO2 to syn-gas. In this work, transition metals dispersed in barium hexaaluminate have shown to be promising new catalysts for dry methane reforming. In this investigation, a series of BaNixAl12-yO19-d catalysts with varying Ni content were prepared by co-precipitation followed by calcination at 1400°C. CO2 reduction by dry methane reforming was carried out to determine catalyst performance as a function of temperature and carbon formation was also quantified after the reforming tests. Results of catalysts characterization, dispersion and surface area, were correlated to catalytic performance.IntroductionEfficient utilization of CO2 can help to decrease global warming. Methane reforming using carbon dioxide has been of interest for many years, but recently that interest has experienced a rapid increase for both environmental and commercial reasons. The use of CO2 provides a source of clean oxygen, which eliminates the need for costly oxygen separation plants. The product of dry reforming is useful syn-gas, which can be used to generate electrical power in a SOFC or in the production of synthetic fuels (hydrocarbons and alcohols). The dry reforming reaction has been known for a long time. Recent publications have reported studies over several catalysts. For example, the CO2 reforming of CH4 over mesoporous nanocrystalline zirconium powders (ZrO2–3%M2Ox; M: Ce, La and K) at 700ºC have shown methane conversion up to 60% (1). Similarly, the effect of Ni content (1–12 wt%) on the surface and catalytic behavior of bimetallic PtNi catalysts supported on ZSM-5 for reforming of methane with CO2 has been studied and report shows a maximum conversion of 16% and catalyst deactivation was observed during the first hour of time on stream (2). In another report, (3) Ni/a-Al2O3 catalyst was tested for syn-gas generation at 750ºC. The maximum methane conversion was 25%."